ASSOCIATION BETWEEN PERSONALITY TRAITS AND SMOKING CIGARETTE AMONG CRITICAL CARE NURSES: ACROSS-SECTIONAL STUDY (Journal of Forensic Medicine & Toxicology, 2024)
Background: Personality traits are related to cigarette  smoking. However, little is known about the link between  smoking and change in personality. Therefore, the present  study examined whether current cigarette smoking is  associated with personality change among nurses.  Methodology: This cross-sectional study was  conducted on 200 nurses working at Baquba Teaching  Hospital and Baladrooz general hospital in Diyala  Governorate, from September15, 2023 to January10,  2024. A non-probability purposive sample technique was  utilizing in current study, the personality traits assessment  toward smoking were assessed using the personality  assessment questionnaire (PAQ). The data were analysed  using Statistical Package for Social Science (SPSS) version  26. Descriptive statistics were used in this study (e.g.,  mean, standard deviation, frequency, and percentage). For  quantitative data Pearson correlation, and the Chisquare  test was employed to determine the degree and direction  of the relationship between the smoking cigarrete and  personality traits among nursing. Results: There were 200 participants whose mean  age (± SD) of 28.97 (±6.695) years old. Moreover, 69.5%  of the participants were aged 20 to 29 years old. 95 %
Keywords: Personality Traits; Smoker; Critical Care Nursing